Efficacy of Fecal Microbiota Transplantation in Irritable Bowel Syndrome: A Meta-Analysis of Randomized Controlled Trials - Wu, Jie; Lv, Liang; Wang, Chunlian (Frontiers in Cellular and Infection Microbiology, 2022)
Background Randomized controlled trials (RCTs) have examined the efficacy of fecal microbiota transplantation (FMT) in irritable bowel syndrome (IBS) with inconsistent results. We performed a meta-analysis to assess both the short- and long-term efficacy of FMT in IBS. Methods MEDLINE, EMBASE, and the Cochrane Central Register were searched through September 2021. RCTs recruiting adult patients with IBS that compared FMT with placebo with dichotomous data of response to therapy were eligible. Dichotomous data were pooled to obtain a relative risk (RR) of symptom not improving after therapy. RR was also pooled for adverse events (AEs). Continuous data were calculated using a mean difference for IBS-Quality of Life (IBS-QoL). GRADE methodology was used to assess quality of evidence. Results The search strategy generated 658 citations. Seven RCTs comprising 472 patients with IBS were included. FMT was not associated with a significant improvement in global symptom in IBS at 12 weeks in comparison with placebo (RR 0.75, 95% CI 0.43–1.31) with high heterogeneity between studies (I2 87%). Subgroup analyses showed that FMT was superior to placebo when administered via colonoscopy or gastroscope (RR 0.70, 95% CI 0.51–0.96; RR 0.37, 95% CI 0.14–0.99, respectively, while FMT was inferior to placebo when administered via oral capsules (RR 1.88, 95% CI 1.06–3.35). FMT induced a significant improvement in IBS-QoL compared to placebo (mean difference 9.39, 95% CI 3.86–14.91) at 12 weeks. No significant difference in the total number of AEs was observed between FMT and placebo (RR 1.20, 95% CI 0.59–2.47). FMT did not significantly improve global symptom in IBS at 1-year follow-up compared with placebo (RR 0.90, 95% CI 0.72–1.12). The GRADE quality evidence to support recommending FMT in IBS was very low. Conclusion IBS patients may benefit from FMT when administered via colonoscopy or gastroscope. FMT may improve the quality of life of IBS. The long-term use of FMT in IBS warrants further investigation. There is very-low-quality evidence to support recommending FMT in IBS.